The Impact of Mobile Technology in the Battle against COVID-19 Successes and Failures - Giansanti, Daniele (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Mobile technology has undergone rapid development in the last decade and immediately found fertile ground for use in digital healthcare applications. The advantages both for citizens and the health domain are many and interconnected. During the pandemic, mobile technology was also useful for minimizing social distancing, epidemiological monitoring through contact tracing, psychological support, and maintaining social relationships. There is a particular need for scholars to focus both on the innovations in this field during the pandemic and on the problems hampering the use of mobile technology to facilitate the correct and effective introduction of this technology into routine clinical programs in stable health care models. All professionals working in this sector were encouraged to contribute with their experiences. This reprint contains contributions from various experts and different fields. Aspects relating to the success and failures of employment, the medical experience, and acceptance are addressed. Particular space was also given to the role of social media, the use of apps (also presenting critical issues), and innovative apps for contact tracing. The digital divide and the infodemic were also investigated along with their impacts on citizens during the pandemic, for example, in following government directives relating to prevention and vaccination. We dedicate the book to all those involved with different roles in digital health.